EFEK MODERASI DEWAN KOMISARIS ANTARA MANAJEMEN LABA RIIL, PROFITABILITAS, LIKUIDITAS DAN LEVERAGE TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Mariana Ulfa Sofwan (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2019)
The purpose of this research was to find out the effect of real earning management, profitability, liquidity and leverage with the board of commissoners as a moderating variable on CSR disclosure and size as a control variable.  This research uses multiple regression testing. The sample is a basic industrial and chemical manufacturing company listed on the Indonesia Stock Exchange by sampling 129 companies from 2015-2017. Sample determination was done by using purposive sampling method. The test of hypothesis using SPSS application. Based on the results of the analysis can be concluded that real earning management, profitability, and liquidity has positive effects on CSR disclosure, while leverage has negative effects on CSR disclosure. The board of comissoners was able to strenghten the positive influence of real earning management and liquidity on CSR disclosure and also able to weaken the negative influence of leverage on CSR disclosure. However, the board of comissoners was unable to strenghten the positive positive influence of profitability on CSR disclosure.